Jenis- Jenis Jamur Endofit Tanaman Jeruk Siam (Citrus nobilis var. microcarpa) di Perkebunan Dungun Prapakan Sambas - Mukarlina, Suliati, Rahmawati, (Universitas Tanjungpura, 2017)
Siam citrus (Citrus nobilis var. microcarpa) is a horticultural plant which becomes superior commodities in Tebas district, Sambas regency, West Kalimantan. Endophytic fungi are present in the plant tissue and can function as biological control agents. This research aimed to find out the types of endophytic fungi contained siam citrus plants in Dungun Perapakan Plantation, Tebas district, Sambas regency. This research lasted for 3 months, from February to April 2016 in Laboratory of Microbiology, Faculty of Mathematics and Natural Sciences, Tanjungpura University, Pontianak. The method used in this research is direct seeding method and fungi identification is based on morphological characteristics macroscopically and microscopically. The results show, that there are 12 types of endophytic fungi from citrus plants (C. nobilis var. microcarpa). The endophytic fungi found were members of the species Aspergillus niger BJ U1, Curvularia sp. DJ U3, Fusarium sp. BJ U2, Fusarium sp. AJ U3, Penicillium sp AJ U2, Nigrospora sp. AJ U1, Mucor sp. AJ U3, Cladosporium sp. AJ U2, Cylindrocladium sp. DJ U3, Acremonium sp. BJ U3 , Colletotrichum sp. AJU2, Rhizopus sp. BJ U3